1978
DOI: 10.1007/bf01317283
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of the Nodamura virus in the larvae of the lepidopteranGalleria mellonella (L.)

Abstract: The pathogenesis and morphogenesis of the Nodamura virus, an insect picorna- virus which can also infect vertebrates such as newborn mice, are described in the larvae of G. mellonella. Examination of thin sections of muscle, salivary and moulting glands, hemocytes adipose tissue and hypodermis of the infected larvae of G. mellonella shows in the cytoplasm the accumulation of viral particles either dispersed or in a stringlike or paracrystalline array. These arrays of virions can be within membrane- bound vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…While not yet visualized at the ultrastructural level, we hypothesize that the clustered phenotype seen in cultured cells represents the same altered mitochondrial morphology and mitochondrial aggregation previously described for NoV-infected muscle tissue (1,43,44). We further showed that NoV RNA synthesis also localizes to these RdRpinduced mitochondrial networks, further establishing mitochondria as the site of viral RC formation.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…While not yet visualized at the ultrastructural level, we hypothesize that the clustered phenotype seen in cultured cells represents the same altered mitochondrial morphology and mitochondrial aggregation previously described for NoV-infected muscle tissue (1,43,44). We further showed that NoV RNA synthesis also localizes to these RdRpinduced mitochondrial networks, further establishing mitochondria as the site of viral RC formation.…”
Section: Discussionmentioning
confidence: 65%
“…Transmission electron micrographs of muscle tissue from NoV-infected mice show localized increases in the number of mitochondria, rearrangement of mitochondrial membranes, and aggregation of mitochondria. Similar rearrangements in muscle tissue are also visible in NoV-infected larvae of the greater wax moth, Galleria mellonella, which exhibit hind segment paralysis upon infection with NoV (1,43,44). However, the role of mitochondria in NoV infection has not been addressed previously.…”
mentioning
confidence: 78%
See 3 more Smart Citations